Balancing the fat: lipid droplets and human disease - Natalie Krahmer; Robert V. Farese; Tobias C. Walther (EMBO Molecular Medicine)
Abstract Lipid droplets (LDs) are dynamic, cytosolic lipid‐storage organelles found in nearly all cell types. Too many or too few LDs during excess or deficient fat storage lead to many different human diseases. Recent insights into LD biology and LD protein functions shed new light on mechanisms underlying those metabolic pathologies. These findings will likely provide opportunities for treatment of diseases associated with too much or too little fat.